PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, LIKUIDITAS DAN INVESTMENT OPPORTUNITY SET (IOS) TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Paulina Warianto; Ch Rusiti (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2014)
The purpose of this study was to determine the efect of frm size, capital structure, liquidity and investment opportunity set (IOS) simultaneously and partially on the quality of earnings. Population in the study was all manufacturing companies listed on the Stock Exchange in 2008-2012. Sampling using purposive sampling technique that is specifc sample selection criteria, so that in can be sampled in this study were 360 companies manufacturing (72 per company). The analytical method used was the multiple linear regression. Te result shows simultaneous testing showed that the size of the company, capital structure, liquidity and investment opportunity set (IOS) efect on earnings quality. Partially, company size and liquidity signifcant positive efect on the quality of earnings. Capital structure and investment opportunity set (IOS) signifcant negative efect on the quality of earnings.Keywords: company size, capital structure, liquidity, investment opportunity set (IOS) and the quality of earnings.